(untitled) (Journal of the College of Languages (JCL), 2019)
The present paper(Spacio-Temporal Relations in the Translated Text in Both Russian and Arabic) focuses on the spacio-temporal effect in the translated text; it is possible to compose the translation text simultaneously with the process of the composing the original text. This is carried out during the simultaneous consecutive translation. And, the time and place of composing the translation might greatly differ from the time and place of composing the original textt. The translator may tackle a text of an ancient time and written in a language which might have changed, and may thus appear as another language where the author might have talked on behalf of a people who had lived or are living in apparently different geographical and climatic conditions from those of the receptor of the translation who belongs to a people having completely different style of life, history, traditions and culture. These should never affect the process of translation. Аннотация Наше исследование фокусируется на временном и пространственном эффекте переведенного текста. Процесс создания текста перевода может выполняться одновременно с процессом создания оригинального текста. Это делается во время синхронного перевода. Время создания и местоположения перевода может сильно отличаться от времени оригинала и его местоположения. Переводчик может иметь дело с текстом древней исторической эпохи и языком, который изменился в течение этого периода в той мере, в какой его статус, кажется, представляет собой другой язык. Автор оригинального текста может быть имеет язык людей, которые жили или живут в других географических и климатических условиях, сильно отличающихся от географических условий получателей перевода, которые имеют совершенно иную структуру жизни, истории, традиции и культуры. Не могут ли такие различия повлиять на процесс перевода ?